I can see clearly now: the effects of age and perceptual load on inattentional blindness - Remington, Anna; Cartwright-Finch, Ula; Lavie, Nilli (Frontiers in Human Neuroscience, 2014)
Attention and awareness are known to be linked (e.g. see Lavie, Beck, & Konstantinou, 2014, for a review). However the extent to which this link changes over development is not fully understood. Most research concerning the development of attention has investigated the effects of attention on distraction, visual search and spatial orienting, typically using reaction time measures which cannot directly support conclusions about conscious awareness. Here we used Lavie’s Load Theory of Attention and Cognitive Control to examine the development of attention effects on awareness. According to Load Theory awareness levels are determined by the availability of attentional capacity. We hypothesised that attentional capacity develops with age, and consequently that awareness rates should increase with development due to the enhanced capacity. Thus we predicted that greater rates of inattentional blindness (IB) would be found at a younger age, and that lower levels of perceptual load will be sufficient to exhaust capacity and cause IB in children but not adults. We tested this hypothesis using an IB paradigm with adults and children aged 7-8, 9-10, 11-12 and 13 years old. Participants performed a line-length judgment task (indicating which arm of a cross is longer) and on the last trial were asked to report whether they noticed an unexpected task-irrelevant stimulus (a small square) in the display. Perceptual load was varied by changing the line-length difference (with a smaller difference in the conditions of higher load). The results supported our hypothesis: levels of awareness increased with age, and a moderate increase in the perceptual load of the task led to greater IB for children but not adults. These results extended across both peripheral and central presentations of the task stimuli. Overall, these findings establish the development of capacity for awareness and demonstrate the critical role of the perceptual load in the attended task.